2011
DOI: 10.1177/0272431611414061
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal Development and Adolescent Girls’ Substance Use

Abstract: To highlight individual and neighborhood interactions in the risk of adolescent substance use, this study examined the moderating role of neighborhood disadvantage on the relationship between pubertal development and adolescent girls' substance use. Drawing on the contextual amplification hypothesis, it was hypothesized that the effect of pubertal development on substance use would vary by level of neighborhood disadvantage and race. The sample included 5,591 adolescent girls from the National Longitudinal Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…There may be other aspects of the neighborhood that are more important among Black girls. Prior work illustrates that pubertal development was positively linked to alcohol use, which was amplified for Black girls residing in high disadvantaged neighborhoods (Tanner-Smith, 2012). Disadvantaged neighborhoods were operationalized economically such as the proportion of single female-headed households, the proportion of households receiving public assistance, and the proportion of persons below the poverty level (see Tanner-Smith, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There may be other aspects of the neighborhood that are more important among Black girls. Prior work illustrates that pubertal development was positively linked to alcohol use, which was amplified for Black girls residing in high disadvantaged neighborhoods (Tanner-Smith, 2012). Disadvantaged neighborhoods were operationalized economically such as the proportion of single female-headed households, the proportion of households receiving public assistance, and the proportion of persons below the poverty level (see Tanner-Smith, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Prior work illustrates that pubertal development was positively linked to alcohol use, which was amplified for Black girls residing in high disadvantaged neighborhoods (Tanner-Smith, 2012). Disadvantaged neighborhoods were operationalized economically such as the proportion of single female-headed households, the proportion of households receiving public assistance, and the proportion of persons below the poverty level (see Tanner-Smith, 2012). The effects of early pubertal maturation were heightened among Black girls who lived in neighborhoods characterized as economically impoverished (Tanner-Smith, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Further, Fagan et al (2014) showed the link between neighborhood factors and increased substance use among adolescents. Neighborhood disadvantage has also been positively associated with substance use among adolescent females (Tanner-Smith, 2012).…”
Section: Dangerous Neighborhoodsmentioning
confidence: 99%
“…In general, there is persuasive evidence of peer mediation processes in studies of pubertal development and various types of adverse outcomes, including depression, school failure, and substance abuse (Cavanagh, Riegle-Crumb, & Crosnoe, 2007;Halpern et al, 2007;Marklein, Negriff, & Dorn, 2009;Tanner-Smith, 2012).…”
Section: Evidence From Prior Researchmentioning
confidence: 99%
“…Research by Haynie (2003) showed that early puberty is particularly strongly related to “party delinquency,” that is, such victimless offending as drinking, smoking, truancy, and disorderly conduct, and that delinquent peer associations and dating behavior are the principal mechanisms accounting for this effect. In general, there is persuasive evidence of peer mediation processes in studies of pubertal development and various types of adverse outcomes, including depression, school failure, and substance abuse (Cavanagh, Riegle-Crumb, & Crosnoe, 2007; Halpern et al, 2007; Marklein, Negriff, & Dorn, 2009; Tanner-Smith, 2012).…”
Section: Evidence From Prior Researchmentioning
confidence: 99%